Media Pembelajaran Interaktif: Duck Hunt Name Picker dan Dampaknya pada Keaktifan Siswa Kelas V Sekolah Dasar - Nada, Siti Akmalia (Maliki Interdisciplinary Journal, 2025)
This research analyzes how the use of the Duck Hunt Name Picker game has an impact on students' active learning in grade V elementary school. Duck Hunt Name Picker is an interactive learning media that combines game elements with the learning process, with students' names being randomly selected to participate in the game. The research results show that this media reduces anxiety, increases teacher-student interaction, and increases student participation. Even though it has proven successful, its implementation still has limitations related to dependence on technology and differences in individual student responses. This study recommends combination with other methods for optimal results. This media is able to create a more enjoyable and dynamic learning atmosphere, which in turn increases student participation significantly.